PENGARUH STOCK SPLIT: ANALISIS LIKUIDITAS SAHAM PADA PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA DENGAN MEMPERHATIKAN PERTUMBUHAN DAN UKURAN PERUSAHAAN - SLAMET LESTARI; EKO ARIEF SUDARYONO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2008)
The objective of this research is to empirically examine about the stock liquidity in the growth firms and non-growth firms also large firms and small firms before and after stock split differing by significant. This research uses 44 public companies that listed at Indonesia Stock Exchange during of 2002- 2006 that conducted stock split. The Sample consists of 25 growth firms and 19 non growth firms and 22 large firms and 22 small firms. The selection sample in this research use purposive sampling method. The liquidity proxy that used is trading volume activity (TVA). The results of this research show that stock liquidity between before and after stock split is not different on three firms groups (non-growth firm, large firm and small firm). While on the growth firm has difference between stock liquidity before and after the stock split.